Plant Resin Delivery by Nanovectors as an Emerging Approach to Boost Solubility, Permeability and Bioavailability - Eleonora Truzzi; Giulia Vanti; Lucia Grifoni; Eleonora Maretti; Eliana Leo; Anna Rita Bilia (Pharmaceutics)
Resins are complex mixtures of natural constituents containing non-volatile and volatile terpenes, in combination with gums and polyphenols, used since ancient times for their medicinal properties. Current research has evidenced their therapeutic value with a plethora of activities. The main limits of resins and their constituents for their clinical use are low water solubility, poor stability and bioavailability. Therefore, nanovectors including vesicles, solid lipid nanoparticles, micelles, nanoemulsions, microemulsions and mesoporic nanoparticles have been investigated to optimize the biopharmaceutical properties after topical or oral administration of resins or fractions from them, including essential oils or single constituents. In this review, we report the results evidencing that developed nanovectors were able to entrap high amounts of resins or their components, modify the release properties, enhance their cellular uptake and penetration across biological barriers and optimize the biopharmaceutical properties. In addition, the resins or their fractions as enhancer penetration molecules can optimize the architecture and properties of nanovectors in their capacity to circumvent biological barriers. Although no clinical studies have been reported until now, nanovectors represent a huge platform for upgrading therapies and emerging new treatments of resins such as wound healing therapy.